2021
DOI: 10.3389/fnagi.2021.633495
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Learning and Memory Ability Induced by a Bilaterally Hippocampal Injection of Streptozotocin in Mice: Involved With the Adaptive Changes of Synaptic Plasticity

Abstract: Background: Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive cognitive decline, psychiatric symptoms and behavioral disorders, resulting in disability, and loss of self-sufficiency.Objective: To establish an AD-like mice model, investigate the behavioral performance, and explore the potential mechanism.Methods: Streptozotocin (STZ, 3 mg/kg) was microinjected bilaterally into the dorsal hippocampus of C57BL/6 mice, and the behavioral performance was observed. The serum concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…In this context, intracerebroventricular (ICV) infusion(s) of streptozotocin (STZ), a diabetogenic compound inducing in a laboratory animal a systemic resistance to insulin, can mimic some pathological aspects observed in brain of sAD subjects. Indeed, adult rodents that underwent STZ infusion develop cerebral accumulation of Aβ [11], increased tau phosphorylation and aggregation [12,13], oxidative stress as revealed by increased levels of malondialdehyde and decreased levels of glutathione [14][15][16], changes in insulin signaling [17], dysmetabolism of glucose and energy production [18][19][20], down-regulation of ChAT activity [21], gliosis [12,22,23], caspase(s) activation and apoptosis [24], alteration in synaptic proteins and long-term cognitive deficits [20,[25][26][27][28]. The insulin/phosphoinositide 3-kinase/protein kinase B/glycogen synthase kinase-3β (insulin/PI3K/AKT/GSK3-β) pathway, which regulates glucose metabolism in the brain [20,29,30], is down-regulated in ICV-infused STZ mice along with inactivation of AMP-activated protein kinase (AMPK) signaling cascade, a kinase acting as master sensor of energy balance in mammalian cells [31].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, intracerebroventricular (ICV) infusion(s) of streptozotocin (STZ), a diabetogenic compound inducing in a laboratory animal a systemic resistance to insulin, can mimic some pathological aspects observed in brain of sAD subjects. Indeed, adult rodents that underwent STZ infusion develop cerebral accumulation of Aβ [11], increased tau phosphorylation and aggregation [12,13], oxidative stress as revealed by increased levels of malondialdehyde and decreased levels of glutathione [14][15][16], changes in insulin signaling [17], dysmetabolism of glucose and energy production [18][19][20], down-regulation of ChAT activity [21], gliosis [12,22,23], caspase(s) activation and apoptosis [24], alteration in synaptic proteins and long-term cognitive deficits [20,[25][26][27][28]. The insulin/phosphoinositide 3-kinase/protein kinase B/glycogen synthase kinase-3β (insulin/PI3K/AKT/GSK3-β) pathway, which regulates glucose metabolism in the brain [20,29,30], is down-regulated in ICV-infused STZ mice along with inactivation of AMP-activated protein kinase (AMPK) signaling cascade, a kinase acting as master sensor of energy balance in mammalian cells [31].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lateral ventricle injection of STZ could induce AD-like behavior in rats [ 32 ] or mice [ 33 37 ], as indicated by significant cognitive impairment and increased Aβ 1-42 accumulation and hyperphosphorylated tau in the hippocampus [ 32 ], along with increased glial activation or decreased expression of synapse-associated protein [ 33 37 ]. In our previous study, STZ was administered via bilateral hippocampal injection, and the mice displayed impaired learning and memory abilities, together with insulin resistance and hyperactivated microglial and alternative synaptic plasticity in the hippocampus [ 38 ]. Consistently, in the present study, our results showed that lateral ventricle injection of STZ mice could induce AD-like behavioral performance in mice, as indicated by the decreased frequency, duration, and distance traveled in the center area and reduced rearing frequency in the OFT, increased immobility in the TST, and the decreased preference index of novel object or arm in the NOR or Y-maze.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic plasticity is a crucial basis for regulating learning and memory functions [ 38 ]. It has long been demonstrated that the expression levels of synapse-related proteins such as Syt-1 and synapsin-1 are significantly reduced in the hippocampal tissues of postmortem AD patients and animal models [ 33 , 37 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic plasticity is the material basis for regulating learning and memory functions [55]. It has been long demonstrated that the expression levels of synapse-related proteins such as Synaptotagmin-1 and Synapsin-1 are signi cantly reduced in the hippocampal tissues of postmortem AD patients and animal…”
Section: Discussionmentioning
confidence: 99%